Characterization of the Infant Immune System and the Influence and Immunogenicity of BCG Vaccination in Infant and Adult Rhesus Macaques - Sarfas, Charlotte; White, Andrew D.; Sibley, Laura; Morrison, Alexandra L.; Gullick, Jennie; Lawrence, Steve; Dennis, Mike J.; Marsh, Philip D.; Fletcher, Helen A.; Sharpe, Sally A. (Frontiers in Immunology, 2021)
In countries where tuberculosis (TB) is endemic, the Bacillus Calmette–Guérin (BCG) vaccine is given close to birth to protect infants and children from severe forms of TB. However, BCG has variable efficacy and is not as effective against adult pulmonary TB. At present, most animal models used to study novel TB vaccine candidates rely on the use of adult animals. Human studies show that the infant immune system is different to that of an adult. Understanding how the phenotypic profile and functional ability of the immature host immune system compares to that of a mature adult, together with the subsequent BCG immune response, is critical to ensuring that new TB vaccines are tested in the most appropriate models. BCG-specific immune responses were detected in macaques vaccinated within a week of birth from six weeks after immunisation indicating that neonatal macaques are able to generate a functional cellular response to the vaccine. However, the responses measured were significantly lower than those typically observed following BCG vaccination in adult rhesus macaques. Infant profiles were skewed towards the activation and attraction of macrophages and monocytes and the synthesis in addition to release of pro-inflammatory cytokines such as IL-1, IL-6 and TNF-α. The frequency of specific immune cell populations changed significantly through the first three years of life as the infants developed into young adult macaques. Notably, the CD4:CD8 ratio significantly declined as the macaques aged due to a significant decrease in the proportion of CD4 T-cells relative to a significant increase in CD8 T-cells. The frequency of both CD4+ and CD8+ T-cells expressing the memory marker CD95, and memory subset populations including effector memory, central memory and stem cell memory, increased significantly as animals matured. Infant macaques, vaccinated with BCG close to birth, possessed a significantly higher frequency of CD14+ classical monocytes and granulocytes which remained different throughout the first three years of life compared to unvaccinated age-matched animals. These findings, along with the increase in monokines following vaccination in infants, may provide an insight into the mechanism by which vaccination with BCG is able to provide non-specific immunity against non-mycobacterial organisms.